Cost-effectiveness of providing measles vaccination to all children in Guinea-Bissau - Stine Byberg; Ane Bærent Fisker; Sanne Marie Thysen; Amabelia Rodrigues; Ulrika Enemark; Peter Aaby; Christine Stabell Benn; Ulla Kou Griffiths (Taylor & Francis Group, 2017)
Background: Measles vaccination is associated with major reductions in child mortality and morbidity. In Guinea-Bissau, to limit vaccine wastage, children are only measles-vaccinated if at least six children aged 9-11 months are present at a vaccination session. Objective: To estimate the incremental cost-effectiveness of providing measles vaccine (MV) to all children regardless of age and number of children present. Methods: We estimated MV coverage among children living in villages cluster-randomized to MV for all children and among children cluster-randomized to the current restrictive MV policy (status quo). Prices of MV and injection equipment were obtained from the United Nations Children's Fund (UNICEF). Cost savings of hospital admissions averted were collected from a sample of health facilities. The non-specific mortality effects of MV were estimated and presented as deaths averted and life years gained (LYG) from providing MV-for-all. Results: MV coverage at 36 months was 97% in MV-for-all clusters and 84% in restrictive MV policy clusters. Conservatively assuming 90% wastage of MV under the MV-for-all policy and 40% under the restrictive MV policy, cost per child vaccinated was USD 3.08 and USD 1.19, respectively. The incremental costs per LYG and death averted of the MV-for-all policy were USD 5.61 and USD 148, respectively. The MV-for-all policy became cost-saving at 88% wastage. Conclusions: Taking the low cost of MV and the beneficial non-specific effects of MV into consideration, a 10-dose MV vial should be reclassified as a '1+ dose vial'. The vial should be opened for a single child, irrespective of age, but can vaccinate up to 10 children.